Mevinolin (lovastatin) potentiates the antiproliferative effects of ketoconazole and terbinafine against Trypanosoma (Schizotrypanum) cruzi: in vitro and in vivo studies. - Urbina, J A (1993)
We have studied the antiproliferative effects of mevinolin (lovastatin), an inhibitor of 3-hydroxy-3-methyl-glutaryl-coenzyme A reductase, on the protozoan parasite Trypanosoma (Schizotrypanum) cruzi and its ability to potentiate the action of specific ergosterol biosynthesis inhibitors, such as ketoconazole and terbinafine, both in vitro and in vivo. Against the epimastigote form in vitro, mevinolin produced a dose-dependent reduction of the growth rate up to 25 microM, but at 50 and 75 microM, complete growth arrest and cell lysis took place after 144 and 96 h, respectively. A systematic study of the effects of mevinolin combined with ketoconazole and terbinafine, which act at different points in the ergosterol biosynthesis pathway, on the proliferation of epimastigotes indicated a synergic action, as shown by concave isobolograms and fractional inhibitory concentration indexes ranging from 0.17 to 0.54. Analysis of the sterol composition and de novo sterol synthesis in control and treated cells by thin-layer and gas-liquid chromatographies showed that the antiproliferative effects of the drug alone and in combination were correlated with the depletion of the endogenous ergosterol pool and particularly with a critical (exogenous) cholesterol/endogenous 4-desmethyl sterol ratio in the cells. When we studied the effects of mevinolin on the amastigote form proliferating inside Vero cells in vitro, only very modest effects on the parasites were observed up to 0.75 microM; above this concentration, significant deleterious effects on the host cells were found. However, when the same concentration of the drug was combined with ketoconazole, it was able to reduce by a factor of 10 the concentration of the azole required to eradicate the parasite (from 10 to 1 nM), again indicating a synergic action. On the other hand, a combination of mevinolin and terbinafine had only additive effects on amastigotes, but a ternary combination of mevinolin, ketoconazole, and terbinafine was again clearly synergistic. In vivo studies with a murine model of Chagas' disease showed that mevinolin can also potentiate the therapeutic effects of ketoconazole in this system; combined treatment with the two drugs at doses that alone offered only limited protection against the parasite was able to essentially eliminate circulating parasites and produce complete protection against death. These results confirm the synergic action against the proliferative stages of T. cruzi both in vitro and in vivo and in vivo of combined ergosterol biosynthesis inhibitors that act at different points in the pathway and suggest that mevinolin combined with azoles, such as ketoconazole, can be used in the treatment of human Chagas' disease.